Pendidikan Teologi dalam Perspektif Kebijakan Pendidikan Developmentalisme di indonesia - Yudha Nata Saputra (Sekolah Tinggi Teologi SAPPI Ciranjang, 2017)
Development in all fields requires a more educated society. Developmentalisme education policy answers the needs of development. How is the link between philosophy, educational theory and educational policy developmentalisme? How well developmentalisme educational practice that has been practiced in the educational environment in Indonesia? The study results showed that neopositivisme educational philosophy and theory of humanism education is the basis for education policy developmentalisme. In the practice of education, educational policy developmentalisme focused on efforts to explore the potential of students, technology-based approach to information and communication is an important tool in the practice of education. In the context of education policy developmentalisme, theological education in Indonesia comes with mission of theology.